In situ Growth Synthesis of CuO@Cu‐MOFs Core‐shell Materials as Novel Low‐temperature NH3‐SCR Catalysts. Issue 3 (9th January 2019) - Yu, Yanke; Chen, Changwei; He, Chi; Miao, Jifa; Chen, Jinsheng
Abstract: Metal oxides@MOFs core‐shell materials were developed for selective catalytic reduction of NO x by NH3 (NH3 ‐SCR). A novel CuO@Cu‐MOFs core‐shell material with CuO as the core and Cu3 (BTC)2 as the shell were rationally designed and synthesized by an in situ growth method and used in NH3 ‐SCR reaction. The prepared CuO@Cu‐MOFs materials combined physicochemical properties of CuO (high NO adsorption stability and excellent surface reducibility) and Cu3 (BTC)2 (large specific surface area and abundant acid sites). In addition, the core‐shell materials held large amounts of Brønsted acid sites and abundant adsorbed NO x intermediate species, which benefited NH3 ‐SCR reaction under low‐temperature. Experimental results demonstrated that CuO@Cu‐MOFs possessed higher low‐temperature catalytic activity than that of pure CuO and Cu3 (BTC)2 . Importantly, CuO@Cu‐MOFs performed satisfied stability in NH3 ‐SCR reaction, which made it to be a potential and promising low‐temperature SCR catalyst. Abstract : All grown up ! CuO@Cu3 (BTC)2 core‐shell materials which combined the advantages of CuO and Cu3 (BTC)2 perform superb low‐temperature catalytic activity in NH3 ‐SCR reaction.